2021
DOI: 10.29333/iji.2021.14439a
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers Perceptions of Using Case Study as a Teaching Method in Educational Technology Course in Saudi Arabia

Abstract: The purpose of this study was to examine preservice teachers' attitudes towards the use of case study method. The study design was action research to investigate the effectiveness of utilizing the case study method. The sample for this study included fourteen master's students enrolled in educational technology in special education course. The results revealed that preservice teachers overall had positive attitudes towards the use of case studies. Also, the case study method was beneficial for improving studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(44 reference statements)
0
5
1
Order By: Relevance
“…Table 1 shows students' responses regarding each of the items in the usefulness category. There are three subcategory presented in the usefulness category: learning, critical thinking and engagement (Almuqayteeb, 2021). Students reported that their engagement in the classroom during the course that implement case study method was lower (3.3) than their learning and critical thinking (3.7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows students' responses regarding each of the items in the usefulness category. There are three subcategory presented in the usefulness category: learning, critical thinking and engagement (Almuqayteeb, 2021). Students reported that their engagement in the classroom during the course that implement case study method was lower (3.3) than their learning and critical thinking (3.7).…”
Section: Resultsmentioning
confidence: 99%
“…The case study method or case method is a teaching and learning method that employs case studies to engage students in actively solving complex problems similar to those encountered in real-life situations (Magwilang, 2022;Pilato & Ulrich, 2014). In many publications, such as journal articles and books, the case study method is referred to by different names, such as case method (Forsgren, Christensen, & Hedemalm, 2014) and case-based instruction (Almuqayteeb, 2021;Magwilang, 2022).…”
Section: Case Study Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case method leads students to explore information in solving cases scientifically, this of course directly shapes students' scientific literacy skills (Rahayu, 2020). The case study method was beneficial for improving student's learning, engagement, and critical thinking (Almuqayteeb, 2021). Improving the long-term memory, enhancing the quality of decision making and understanding the individual differences of individuals are the advantages of case method teaching (Afsouran et al, 2018).…”
Section: Figure 2 Scientific Literacy Ability By Contentmentioning
confidence: 99%